Manifestation Of The Creative Legacy In The Contemporary Thought And Creativity Dr. Abdul-Rahman Al-Basha Providing Amodel - AL-Hasan, Hassan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The Arab Literary Heritage Is An Inexhaustible Source Inspiring A Great Deal Of Intellectual And Creative Facts Which Enrich The Ear Innovation. Thus, Dr. Abdul-Rahman Al-Basha Is One Of The Arab Intellectual Who Took A Look At The Arab Heritage And Assimilated It, Adding Intellectual, Critical And Literary Visions That Contributed To The Enrichment Of The Arab Library With The Importance Of This Heritage And What Originality It Has, Which Makes The Arabic Literature Grow Firm Roots. The Various Studies Weren,T Also Restricted To Clarifying The Heritage Importance, But They Came To Remove What Got Stuck In The Mind, Clearing Them Of Obstacles And Accusations With The Arab Thought Was Charged To Show The Ability Of Arab Writers And Intellectuals, And Dr. Abdul-Rahman Al-Basha Is On Of Them- Defending The Nation,S Creativity And Thinking Whether In Poetry Or In Thought In A Way That Serves The Intellectual And Cultural Development Of The Arab Nation Throughout History.